“Outwitting the Karmic Impressions; Knowledge Merges into The Source of Its' Creation” (Texas Journal of Philology, Culture and History, 2023)
The wellspring of all knowledge and the secret to advancement is inner wisdom. We may reach the fundamental understanding, which is unchanging, limitless, and eternal when we are calm and silent. We may access the infinite source of wisdom, which is 5 dimensional in nature and from which all knowledge flows and makes 3D life possible, by concentrating our energies and evading karmic patterns. These concepts are not grounded in mainstream scientific understanding and are more spiritual, philosophical, and metaphysics. They represent a perspective explored in various traditions and new-age beliefs. Interpretations and opinions can vary among individuals and cultures, and they can provide a framework for understanding personal experiences and perceptions of reality. To explore these ideas further, engage with philosophical and spiritual texts, meditative practices, and discussions with people with similar beliefs. Approaching these concepts with an open mind and critical discerning perspective is essential